Atensi Siswa Dalam Menyelesaikan Masalah Fungsi - Syafruddin Kaliky; Patma Sopamena; Fahruh Juhaevah; Nurlaila Sehuwaky; Kasliyanto (KALAMATIKA Jurnal Pendidikan Matematika, 2020)
This study aims to describe the students' attention processes in solving functional problems. This research is a qualitative descriptive study, with subjects of 2 students taken from 8 students of secondary school. The results show that the students' attention process in solving functional problems was based on attentional characteristics, namely when students who answered correctly in solving questions and interview process, before and after reflection had complete cognitive attention structures. While students who answer incorrectly in solving problems have incomplete attention to cognitive structures, characterized by a lack of concentration in seeing the relationship between one mathematical object and another mathematical object. Attention characteristics in this study begin with recalling previous information and responding or giving feedback to problems by linking previous information with existing problems. Next analyze by breaking down information into smaller parts and easy to understand. The next step looks at the relationship between the decomposition process to get ways that can be used in the settlement process to obtain the final results that are part of decision making.